Lysine methylation： beyond histones - Zhang, Xi; Wen, Hong; Shi, Xiaobing (Acta biochimica et biophysica Sinica, 2012)
Posttranslational modifications （PTMs） of histone proteins, such as acetylation, methylation, phosphorylation, and ubiquitylation, play essential roles in regulating chromatin dynamics. Combinations of different modifications on the histone proteins, termed ＇histone code＇ in many cases, extend the information potential of the genetic code by regulating DNA at the epigenetic level. Many PTMs occur on non-histone proteins as well as histones, regulating protein-protein interactions, stability, localization, and/or enzymatic activities of proteins involved in diverse cellular processes. Although protein phosphorylation, ubiquitylation, and acetylation have been extensively studied, only a few proteins other than histones have been reported that can be modified by lysine methylation. This review summarizes the current progress on lysine methylation of non- histone proteins, and we propose that lysine methylation, like phosphorylation and acetylation, is a common PTM that regulates proteins in diverse cellular processes.